Persepsi Guru Geografi tentang Penerapan Program Sekolah Penggerak pada SMA Negeri di Kabupaten Indragiri Hilir, Provinsi Riau - Triska, Epa; Suasti, Yurni (Lembaga Yasin AlSys, 2025)
The Sekolah Penggerak Program is a strategic government initiative aimed at transforming the education system through holistic interventions at the school level. However, variations in school contexts and resource readiness have led to differing perceptions regarding its implementation. This study aims to describe geography teachers’ perceptions of the Sekolah Penggerak Program, focusing on aspects of understanding, intervention application, impact, and implementation challenges. A descriptive qualitative approach was employed, using purposive sampling to select 26 informants from five state senior high schools implementing the program in Indragiri Hilir Regency, Riau Province. Data were collected through interviews and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that geography teachers have a solid understanding of the program's core components. Dialogical mentoring from facilitators, intensive training, and active participation in learning communities have contributed to enhanced teacher competence and collaboration. A shift in learning paradigms toward more student-centered and active approaches is evident, marked by the use of assessment-based planning, reflective practices, and the integration of technology. Nonetheless, limited infrastructure, administrative workload, and disparities in teacher readiness pose significant implementation challenges. Despite these obstacles, teachers demonstrate a strong commitment to continuous adaptation. These findings highlight the need for responsive education policies and sustained teacher capacity development programs to support the successful transformation of education at the school level.